IoT medical device risks: Data security, privacy, confidentiality and compliance with HIPAA and COBIT 2019 - Na-ella Khan; Riaan J. Rudman (South African Journal of Business Management, 2025)
Purpose: This study aimed to develop a comprehensive framework to enable the identification of risks pertaining to data security, privacy and confidentiality when using medical Internet of Things (IoT) devices.